Developing a Test to Measure Mathematical Reasoning Among High School Students - Saeedullah, Rafaqat Ali Akbar, (JSE, 2023)
Mathematical reasoning has become an essential tool for secondary school students to excel in every walk of life. A valid measuring tool is a basic need to measure mathematical reasoning. The objective of the present study was to develop a valid and reliable instrument to measure mathematical reasoning among high school students.